+0  
 
0
76
4
avatar+30 

 

If \(f(x)=3x-7\) then what is \(f^{-1}(f^{-1}(-1))? \)

 Nov 24, 2022
 #2
avatar+118203 
+3

 

If   \(f(x)=3x-7\)     then find    

 

\(f^{-1}(f^{-1}(-1))?\)

 

Let

\(y=3x-7\\ \frac{y+7}{3}=x\\ x=\frac{y+7}{3}\\ so\;if\;\\ f(x)=3x-7\\ then\\ f^{-1}(x)=\frac{x+7}{3}\\ f^{-1}(-1)=\frac{-1+7}{3}\\ f^{-1}(-1)=2\\ f^{-1}f^{-1}(-1)=f^{-1}(2)=9/3 = 3 \)

 

 

 

 

f(x)=3x-7

f^{-1}(f^{-1}(-1))?

 Nov 25, 2022
 #4
avatar+30 
+2

Thanks, Melody! I understand now

Ninchux  Nov 26, 2022
 #3
avatar+118203 
+3

Here is a graphical representation of what is happening.

 

 Nov 25, 2022

18 Online Users